The scaling relationship between leaf nitrogen and phosphorus concentrations in vascular epiphytes - Hu, T.; Zhang, T. T.; Tang, D. D.; Liu, S.; Li, S.; Hu, X. W.; Mo, Y. X.; Liu, W. Y. (Frontiers in Plant Science, 2026)
IntroductionThe scaling relationship between leaf nitrogen (N) and phosphorus (P) concentrations reflects plant adaptation strategies and evolutionary dynamics. While extensively studied in terrestrial plants, vascular epiphytes—a key yet understudied component of global biodiversity—remain poorly understood.MethodsWe compiled leaf N and P data from 38 epiphyte species across tropical seasonal rainforests and subtropical montane forests in China, supplemented by a global literature synthesis. Standardized major axis (SMA) regression analyzed N-P scaling exponents (β) across forest types, functional groups, and habitats.ResultsEpiphytes exhibited a distinct global N-P scaling exponent (β=0.78), significantly higher than terrestrial plants. Facultative epiphytes showed lower β in epiphytic (0.69) versus terrestrial habitats (0.91). No significant variation occurred among functional groups or forest types, suggesting conserved nutrient allocation strategies.DiscussionThe elevated β underscores epiphytes’ reliance on atmospheric nutrient inputs and adaptive P retention. Habitat-driven differences highlight niche specialization, while functional group uniformity reflects stoichiometric constraints of canopy living. These findings redefine epiphyte nutrient ecology within broader plant stoichiometry theory.